2014
DOI: 10.1007/s00248-013-0352-7
|View full text |Cite
|
Sign up to set email alerts
|

Southern Appalachian Peatlands Support High Archaeal Diversity

Abstract: Mid-latitude peatlands with a temperate climate are sparsely studied and as such represent a gap in the current knowledge base regarding archaeal populations present and their roles in these environments. Phylogenetic analysis of the archaeal populations among three peatlands in the Southern Appalachians reveal not only methanogenic species but also significant populations of thaumarchaeal and crenarchaeal-related organisms of the uncultured miscellaneous crenarchaeotal group (MCG) and the terrestrial group 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 124 publications
1
8
1
Order By: Relevance
“…There are only a few studies, mainly about waterlogged soils, reporting the MCG constituting a mentionable proportion of the archaeal soil community (summarized by Kubo et al, 2012 in the Supplementary Information). In peatland soils of the Appalachian Mountains not only Archaea of the Group 1.1c and SAGMCG-1 were detected but also MCG with a proportion of 37% (Hawkins et al, 2014). Another study about permafrost soils analyzed the archaeal community in different soil depths and reported that 26–73% of the sequences were affiliated to MCG -OTUs corresponding to our high proportions (Wei et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies, mainly about waterlogged soils, reporting the MCG constituting a mentionable proportion of the archaeal soil community (summarized by Kubo et al, 2012 in the Supplementary Information). In peatland soils of the Appalachian Mountains not only Archaea of the Group 1.1c and SAGMCG-1 were detected but also MCG with a proportion of 37% (Hawkins et al, 2014). Another study about permafrost soils analyzed the archaeal community in different soil depths and reported that 26–73% of the sequences were affiliated to MCG -OTUs corresponding to our high proportions (Wei et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…pH may be "the" driver, or one of the most important ones, in addition to organic carbon substrates, determining the distribution of the I.1c Thaumarchaeota. Thus, the I.1c cluster is not restricted to only boreal forest soils, but have also been detected in various mature and unmanaged grassland soils, where the soil pH has been maintained below 5 [27,44,[46][47][48] and even in acidic subtropical and tropical peatland soils [29,30].…”
Section: Phmentioning
confidence: 95%
“…The I.1c group has been found in many environments, but have been considered boreal Archaea due to the initial discovery of this group in acidic (pH 3.5-5) boreal forest soil [9], the so-called Finnish Forest Soil, or FFS, group. Later this group has been detected with increasing frequency and found in many acidic soil (reviewed in [26]) and aquatic environments [27], as well as from deep peat (280 cm) from boreal fens [28], shallow peat from elevated oligotrophic subtropical bogs [29], and even tropical peat swamp forest soils [30], where they have been found to represent up to almost 50% of the archaeal community.…”
Section: The Influence Of the Season On The Abundance Of Thaumarchaeomentioning
confidence: 99%
“…Methanomassiliicoccus luminyensis B10: CAJE01000003 (Edwards et al, 1998;Hales et al, 1996), Russia (Kotsyurbenko et al, 2007), Scandinavia Høj et al, 2005), the United States (Basiliko et al, 2003;Cadillo-Quiroz et al, 2006;Hawkins et al, 2014) 2006). Further, this group tends to dominate in ombrotrophic bogs and is often outcompeted in minerotrophic fens, where the methanogenic community becomes more diverse Kotsyurbenko, 2010;Kotsyurbenko et al, 2007).…”
Section: Methanoregula Boonei 6a8: Yp_001403604mentioning
confidence: 99%